Prospects for Comprehensive Screening and Treatment of Cervical Cancer - S. A. Begliarzade; R. R. Mukhametova; B. Zhao (Креативная хирургия и онкология)
Cervical cancer, the second most common malignancy in women, poses a serious problem, especially for less developed countries. This results in the suffering of patients and their families, as well as causing social and global consequences. The present review aims to highlight the importance of preventing and treating cervical cancer, outline current problems and challenges, and indicate prospects for improvement. To this end, we analyzed available online data on cervical cancer screening and treatment in Russia (keyword search) and abroad (keyword search in PubMed, http://pubmed. ncbi.nlm.nih.gov/). The study examines the economic and health conditions of various countries, identifying nuances and challenges in implementing screening programs. In spite of significant reductions in cervical cancer incidence and mortality in developed countries due to screening and vaccination initiatives, other regions are still faced with a number of problems. The focus on vaccination and a comprehensive strategy indicates the need for a concerted effort. Further efforts are required in the fight against cervical cancer. While progress has been made in some regions, the health care system of developing countries, including Russia, requires constant improvement of screening and treatment methods, as well as coordination of efforts.